Disparities in Cancer Survival Among Adolescents and Young Adults: A Population-Based Study of 88 000 Patients. (23rd January 2021) - Murphy, Caitlin C; Lupo, Philip J; Roth, Michael E; Winick, Naomi J; Pruitt, Sandi L
Abstract: Background: Adolescents and young adults (AYA, aged 15-39 years) diagnosed with cancer comprise a growing, yet understudied, population. Few studies have examined disparities in cancer survival in underserved and diverse populations of AYA. Methods: Using population-based data from the Texas Cancer Registry, we estimated 5-year relative survival of common AYA cancers and examined disparities in survival by race and ethnicity, neighborhood poverty, urban or rural residence, and insurance type. We also used multivariable Cox proportional hazards regression models to examine associations of race or ethnicity, neighborhood poverty, urban or rural residence, and insurance type with all-cause mortality. Results: We identified 55 316 women and 32 740 men diagnosed with invasive cancer at age 15-39 years between January 1, 1995, and December 31, 2016. There were disparities in relative survival by race and ethnicity, poverty, and insurance for many cancer types. Racial and ethnic disparities in survival for men with non-Hodgkin lymphoma (74.5% [95% confidence interval (CI) = 72.1% to 76.7%] White vs 57.0% [95% CI = 51.9% to 61.8%] Black) and acute lymphocytic leukemia (66.5% [95% CI = 61.4% to 71.0%] White vs 44.4% [95% CI = 39.9% to 48.8%] Hispanic) were striking, and disparities remained even for cancers with excellent prognosis, such as testicular cancer (96.6% [95% CI = 95.9% to 97.2%] White vs 88.7% [95% CI = 82.4% to 92.8%] Black). In adjusted analysis, being Black or Hispanic, living in high-poverty neighborhoods, and having Medicaid, other government insurance, or no insurance at diagnosis were associated with all-cause mortality in both women and men (all 2-sided P < .01). Conclusions: Our study adds urgency to well‐documented disparities in cancer survival in older adults by demonstrating persistent differences in relative survival and all-cause mortality in AYAs. Findings point to several areas of future research to address disparities in this unique population of cancer patients.